Effective Classroom Management in Physical Education: Strategies for Beginning Teachers. Issue 8 (13th October 2018) - Grube, Dan; Ryan, Stu; Lowell, Sarah; Stringer, Amy
Abstract : Classroom management is often a big concern for beginning teachers. Beginning teachers often worry about how they will uphold the same level of classroom management as veteran teachers. Because of this, classroom management strategies for beginning teachers can be useful to get a program started and lead to more productive and successful learning experiences for students. In this article, classroom management strategies for beginning teachers will be discussed, including equipment protocols, classroom procedures, routines and how to deal with inappropriate behaviors.